PERANAN MATA KULIAH AUDITING DALAM MENGURANGI EXPECTATION GAP - Maylia Pramono Sari (UKDW, 2008)
Expectation Gap is the different between what is believed by community and the financial statement user as auditor "responsibility with what is believed by auditor as thier's responsibility (AICPA,1991). Expectation Gap between auditor and community and financial statement user is occur in Indonesi, so this subject in universtity degreecan reduce the differences. Based on problem description in this research, the goal of this research is to prove the difference about perception of auditor's role and responsibility. And the other goal is to find the specific process of auditing which has done by the student in the beginning of subject and at the end of the subject of auditing. The result of the research shows that perception about auditor's role and responsibilities, include process of the auditing. The accounting student, who has not jointed the subject is signifiantly different with the perception og accounting student is significantly different with the perception og accounting student who has jointed the subject. hypothesis test is using Wilcoxon Rank Test. In the Wilcoson Rank Test which the probability < 0,05, so H1 accepted.